Implementasi Pendekatan Bermain dalam Meningkatkan Keterampilan Sosial Anak di TK Islam Al-Fitriyah - Elsa Noviani; Ai Suryani; Yuni Nurhalimah; Reni Nuraeni; Saadah, Saadah (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
Early childhood education plays a crucial role in developing children's social skills, which serve as the foundation for their interactions and adaptation in social environments. One effective approach to enhancing social skills is the play-based approach. This study aims to analyze the implementation of the play-based approach in improving children's social skills at TK Islam Al-Fitriyah. This research employs a qualitative method with a field study design. Data collection techniques include observations, interviews with teachers and parents, and documentation of children's play activities. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the play-based approach, particularly role-playing, group games, and educational games, is effective in enhancing children's social skills. Children become more capable of cooperating, communicating, sharing, and demonstrating empathy toward their peers. The study's findings affirm that a learning environment that supports play has a positive impact on children's social interactions. The conclusion of this study emphasizes that the play-based approach is an appropriate strategy for improving young children's social skills. Recommendations are provided for educators to further optimize this method in the learning process.